Integrase Strand Transfer Inhibitors Are Associated With Incident Diabetes Mellitus in People With Human Immunodeficiency Virus. (6th May 2022) - O'Halloran, Jane A; Sahrmann, John; Parra-Rodriguez, Luis; Vo, Daniel T; Butler, Anne M; Olsen, Margaret A; Powderly, William G
Abstract: Background: Integrase strand transfer inhibitors (INSTIs) are associated with weight gain in people with HIV (PWH). Less is known about the risk of other metabolic outcomes such as diabetes mellitus and hyperglycemia. Methods: IBM® MarketScan® databases for commercially and Medicaid-insured adults were used to identify PWH newly initiating antiretroviral therapy (ART). The primary outcome was a composite of new-onset diabetes mellitus/hyperglycemia in the 6 months following ART initiation and was identified using International Classification of Disease, Ninth revision, Clinical Modification (ICD-9-CM) and ICD-10-CM diagnosis and procedure codes and Current Procedural Terminology, 4th Edition (CPT-4) codes. To examine the relationship between INSTI use and the composite outcome, we estimated the risk using Cox proportional hazards models with calendar time-specific standardized mortality ratio weights. Results: Of 42 382 PWH who initiated ART between 1 July 2007 and 30 June 2018, 22 762 (54%) were treated with INSTI-based regimens. Mean age was 38 years, 74% were male, and 19% were Medicaid insured. PWH on INSTIs were 31% more likely to develop new-onset diabetes mellitus/hyperglycemia (hazard ratio [HR], 1.31; 95% confidence interval [CI], 1.15–1.48]) compared with those who initiated non–INSTI-based regimens. When examined individually, the highest risk was associated with elvitegravir (HR, 1.54; 95% CI, 1.32–1.97; P < .001) and the lowest risk with raltegravir (HR, 1.19; 95% CI, 1.03–1.37; P = .02). Conclusions: INSTI use was associated with increased risk of new-onset diabetes mellitus/hyperglycemia in the 6 months following ART initiation. Abstract : Integrase strand transfer inhibitor (INSTI)-based regimens are associated with increased risk of new-onset diabetes mellitus/hyperglycemia in the 6 months following antiretroviral therapy initiation when compared with non–INSTI-based regimens